2014
DOI: 10.1111/gcbb.12142
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and harvest effects on soil properties under rainfed switchgrass and no‐till corn over 9 years: implications for soil quality

Abstract: Nitrogen fertilizer and harvest management will alter soils under bioenergy crop production and the long-term effects of harvest timing and residue removal remain relatively unknown. Compared to no-tilled corn (NT-C, Zea mays L.), switchgrass (Panicum virgatum L.) is predicted to improve soil properties [i.e. soil organic C (SOC), soil microbial biomass (SMB-C), and soil aggregation] due to its perennial nature and deep-rooted growth form, but few explicit field comparisons exist. We assessed soil properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 52 publications
5
64
3
2
Order By: Relevance
“…The index values from this study (Table 3) fit within existing ranges found in agricultural soils in this region (Hammac et al, 2016;Jokela et al, 2011;Karlen et al, 2014bKarlen et al, , 2017Stewart et al, 2015). Generally, higher index values suggest improved soil functioning.…”
Section: Soil Management Assessment Framework Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…The index values from this study (Table 3) fit within existing ranges found in agricultural soils in this region (Hammac et al, 2016;Jokela et al, 2011;Karlen et al, 2014bKarlen et al, , 2017Stewart et al, 2015). Generally, higher index values suggest improved soil functioning.…”
Section: Soil Management Assessment Framework Analysissupporting
confidence: 79%
“…Though these four studies were not focused on stover removal in continuous corn, the results offer a useful comparison with other agricultural soils. Stewart et al (2015) included corn stover removal at a marginally productive site in Nebraska. The no-till 50% residue removal rate lowered soil quality index scores for SOC, aggregate stability, and MBC compared with no residue removal.…”
Section: Soil Management Assessment Framework Analysismentioning
confidence: 99%
“…Use of perennial grasses on landscapes, especially where soils are marginally productive and/or erosion prone, has been shown to enhance SOC storage and nutrient retention (i.e., P), improve soil bulk density, and reduce erosion risk [45,89,99]. Although direct plant measurements of switchgrass grown under higher atmospheric CO 2 concentrations indicate that switchgrass may be limited in its potential to boost productivity as atmospheric CO 2 concentrations increase [100], model simulations of drought-tolerant cultivars predict switchgrass could withdraw between 3 and 19 % less water than conventional crops under future climate change scenarios [101].…”
Section: System Sustainability and Climate Change Mitigation Potentialmentioning
confidence: 99%
“…Corn stover is currently the feedstock of choice due to its current widespread availability and economic potential [2, 10]. Switchgrass is a promising perennial bioenergy crop that can be grown on marginal lands [11] and provides superior environmental benefits compared to corn, including support for biological diversity [12], lower nitrous oxide emissions [13], and improved soil properties [14, 15]. In order to investigate how interannual variation in precipitation influences the processing characteristics and microbial fermentation of these two important biofuel feedstocks, we compared switchgrass and corn stover that were harvested following the 2012 Midwestern US drought to those harvested during two non-drought years with different precipitation patterns (2010 and 2013).…”
Section: Introductionmentioning
confidence: 99%